Lead-free glass powder for low-resistance ruthenium-series resistance paste, preparation method and application of lead-free glass powder, and low-resistance ruthenium-series resistance paste
By using lead-free glass powder as glass binder and adjusting its composition and preparation process, the problem of TCR value regulation in low-resistance ruthenium-based resistive slurry and the problem of mismatching thermal expansion properties of the ceramic substrate and the resistor body are solved, and the high accuracy and environmental protection performance of the resistor are achieved.
Patent Information
- Application Number
- CN202411612165.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-03-04
AI Technical Summary
In the existing low-resistance ruthenium-based resistive slurry, the resistance temperature coefficient (TCR) value is difficult to effectively regulate, resulting in a large change in the resistor resistance with temperature. At the same time, the thermal expansion of the ceramic substrate and the resistor body does not match, affecting adhesion.
Lead-free glass powder is used as the glass binder. By adjusting its composition and preparation process, the thermal expansion coefficient of the glass powder is reduced, thereby adjusting the TCR value and improving the matching between the ceramic substrate and the resistor.
It effectively reduces the TCR value of the resistor paste, improves the matching of the resistor body and the ceramic substrate, improves the stability and performance of the resistor, and the lead-free formula is environmentally friendly and feasible.
Smart Images

Figure CN119551908A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of resistor pastes, and specifically relates to a lead-free glass powder for low-resistance ruthenium-based resistor paste, a preparation method and application thereof, and low-resistance ruthenium-based resistor paste. Background Art
[0002] Integrated circuits are an important part of the development of modern electronic technology, and thick-film hybrid integrated circuits are an important component of integrated circuits. As the basic material of electronic components, electronic pastes are also widely used in thick-film hybrid integrated circuits. As the most important component in thick-film circuits and hybrid integrated circuits, thick-film resistors were developed the earliest and have the most mature manufacturing technology.
[0003] Ruthenium resistor paste is a thick film resistor paste widely used in the electronics industry. It has the advantages of high resistance stability, good thermal stability, wide resistance range, and good process repeatability. The deviation of the resistance temperature coefficient of ruthenium resistor paste used for high-power and high-precision resistors from the zero value must be as small as possible, otherwise the resistance value of the resistor will change greatly with temperature.
[0004] In the existing low-resistance ruthenium resistor paste, the temperature coefficient of resistance (TCR) value is mainly regulated by adding metal oxides such as copper oxide, niobium pentoxide, titanium dioxide, and manganese dioxide. However, the addition of these metal oxides will increase the square resistance of the resistor paste and may even react with the ceramic substrate to deteriorate its wettability, resulting in poor adhesion between the paste and the substrate. If the TCR is regulated by changing the composition of the glass binder, the above problems can be solved. The glass binder traditionally used for ruthenium resistor paste contains a large amount of lead. The high lead content limits the application range of thick film resistors and is harmful to the human body and the environment. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a lead-free glass powder for low-resistance ruthenium resistor paste, a preparation method and application thereof, and a low-resistance ruthenium resistor paste. The lead-free glass powder serves as a glass binder in the low-resistance ruthenium resistor paste to reduce the thermal expansion coefficient and the temperature coefficient of resistance (TCR), thereby solving the problems of large temperature coefficient of resistance of ordinary low-resistance resistors and poor matching between the resistor body and the ceramic substrate.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention also provides a lead-free glass powder for low-resistance ruthenium-based resistor paste, the preparation raw materials include basic components and additives;
[0008] The basic components include, based on 100% by mass, 50-65% silicon dioxide, 20-30% calcium oxide, 8-12% aluminum oxide, 4-6% boron trioxide, 1-3% magnesium oxide, 1-2% sodium oxide and 0.2-0.5% potassium oxide;
[0009] The mass of the additive is 2-6% of the mass of the basic component;
[0010] The additives include barium oxide and / or zinc oxide;
[0011] The softening temperature of the lead-free glass powder for the low-resistance ruthenium resistor paste is 550-730° C., and the particle size is ≤5 μm.
[0012] The present invention also provides a method for preparing the lead-free glass powder for the low-resistance ruthenium-based resistor paste described in the above technical solution, comprising the following steps:
[0013] Silicon dioxide, calcium oxide, aluminum oxide, boron oxide, magnesium oxide, sodium oxide, potassium oxide and additives are mixed according to mass percentage, and first ball milling, first drying and first crushing are performed in sequence to obtain a mixed powder;
[0014] The mixed powder is melted and then quenched to obtain glass slag;
[0015] After the glass slag is crushed, a second ball milling, a second drying and a second crushing are sequentially performed to obtain the lead-free glass powder for the low-resistance ruthenium-based resistor paste.
[0016] Preferably, the smelting is as follows: first heating the temperature to 900-1000° C., then heating the temperature to 1300-1500° C. for heat preservation; the heat preservation time is 2 hours.
[0017] Preferably, the heating rate of the first heating is 8-10°C / min; the heating rate of the second heating is 5-7°C / min.
[0018] The present invention also provides the use of the lead-free glass powder for low-resistance ruthenium resistor paste described in the above technical solution or the lead-free glass powder for low-resistance ruthenium resistor paste prepared by the preparation method described in the above technical solution in the preparation of low-resistance ruthenium resistor paste.
[0019] The present invention also provides a low-resistance ruthenium resistor paste, comprising a conductive functional phase, a glass bonding phase and an organic carrier;
[0020] The glass bonding phase is the lead-free glass powder for low-resistance ruthenium-based resistor paste described in the above technical solution or the lead-free glass powder for low-resistance ruthenium-based resistor paste prepared by the preparation method described in the above technical solution.
[0021] Preferably, the mass ratio of the conductive functional phase, the glass bonding phase and the organic carrier is 60-70:10-15:15-20.
[0022] Preferably, the conductive functional phase comprises: silver, palladium, bismuth ruthenate and manganese dioxide.
[0023] Preferably, the organic carrier comprises: an organic solvent, a thickener and an organic additive.
[0024] Preferably, the organic solvent includes terpineol and / or butyl carbitol acetate; the thickener is ethyl cellulose; and the organic additive is soybean lecithin and / or oleic acid.
[0025] The present invention provides a lead-free glass powder for low-resistance ruthenium resistor paste, and the raw materials for preparation include basic components and additives; in terms of mass percentage of 100%, the basic components include: 50-65% silicon dioxide, 20-30% calcium oxide, 8-12% aluminum oxide, 4-6% boron trioxide, 1-3% magnesium oxide, 1-2% sodium oxide and 0.2-0.5% potassium oxide; the mass of the additive is 2-6% of the mass of the basic components; the additive includes barium oxide and / or zinc oxide; the softening temperature of the lead-free glass powder for low-resistance ruthenium resistor paste is 550-730°C, and the particle size is ≤5μm. The present invention reduces the thermal expansion coefficient of the glass powder by adding additives. The smaller the thermal expansion coefficient of the glass is compared with the conductive functional phase, the closer the conductive functional phases tend to be to each other when the temperature rises, which offsets the potential barrier between the conductive functional phases due to the temperature increase to a certain extent, reduces the contact resistance, and thus reduces the TCR of the resistor paste. The thermal expansion coefficients of the ceramic substrate and the conductive functional phase are generally quite different. A glass binder with a suitable thermal expansion coefficient can not only regulate the TCR to a certain extent, but also play a transition role, so that the conductive functional phase can be better connected to the ceramic substrate, solving the problem of thermal expansion mismatch between the resistor and the ceramic substrate. The present invention reduces the thermal expansion coefficient of the glass binder by changing the components of the glass binder, effectively achieving a reduction in TCR, solving the problems of large resistance temperature coefficient of ordinary low-resistance resistors and poor matching between the resistor and the ceramic substrate. In addition, the lead-free formula prevents the glass powder from producing lead pollution, achieving environmental friendliness while meeting the performance requirements of high-precision low-resistance resistor products, and can be applied to high-precision low-resistance resistor products. The results of the examples show that the lead-free glass powder for the low-resistance ruthenium resistor slurry provided by the present invention can be applied to low-resistance resistors of 1 to 10Ω / □, and the TCR variation value is 0 to 400×10 -6 / ℃. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a muffle furnace melting curve diagram in Example 1 of the present invention;
[0027] Figure 2 Schematic diagram of the conductive mechanism of low-resistance ruthenium resistor paste, wherein: 1. glass phase; 2. conductive phase. DETAILED DESCRIPTION
[0028] The present invention provides a lead-free glass powder for low-resistance ruthenium resistor paste, and the raw materials for preparation include basic components and additives;
[0029] The basic components include, based on 100% by mass, 50-65% silicon dioxide, 20-30% calcium oxide, 8-12% aluminum oxide, 4-6% boron trioxide, 1-3% magnesium oxide, 1-2% sodium oxide and 0.2-0.5% potassium oxide;
[0030] The mass of the additive is 2-6% of the mass of the basic component;
[0031] The additives include barium oxide and / or zinc oxide;
[0032] The softening temperature of the lead-free glass powder for the low-resistance ruthenium resistor paste is 550-730° C., and the particle size is ≤5 μm.
[0033] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used, and commercially available products known to those skilled in the art may be used.
[0034] The raw materials for preparing the lead-free glass powder for the low-resistance ruthenium-based resistor paste provided by the present invention include basic components.
[0035] As an embodiment, based on 100% by mass, the basic components include: 50-65% silicon dioxide, 20-30% calcium oxide, 8-12% aluminum oxide, 4-6% boron trioxide, 1-3% magnesium oxide, 1-2% sodium oxide and 0.2-0.5% potassium oxide.
[0036] As another embodiment, based on 100% by mass, the basic components include: 55% silicon dioxide, 27% calcium oxide, 10% aluminum oxide, 4.4% boron trioxide, 2% magnesium oxide, 1.2% sodium oxide and 0.4% potassium oxide.
[0037] The raw materials for preparing the lead-free glass powder for the low-resistance ruthenium-based resistor paste provided by the present invention include additives.
[0038] As an embodiment, the mass of the additive is 2-6% of the mass of the basic component, and in specific embodiments, it is 2%, 4% or 6%; the additive includes barium oxide and / or zinc oxide, and in specific embodiments, it is barium oxide or zinc oxide.
[0039] As an implementation mode, the softening temperature of the lead-free glass powder for the low-resistance ruthenium resistor paste is 550-730° C., and in a specific embodiment, it is 600-700° C., and the particle size is ≤5 μm, and in a specific embodiment, it is 5 μm.
[0040] The present invention reduces the thermal expansion coefficient of glass powder by adding additives. The smaller the thermal expansion coefficient of glass is compared with the conductive functional phase, the closer the conductive functional phases tend to be to each other when the temperature rises, which offsets the potential barrier between the conductive functional phases due to the temperature increase to a certain extent, reduces the contact resistance, and thus reduces the TCR of the resistor paste. The thermal expansion coefficients of the ceramic substrate and the conductive functional phase are generally quite different. The glass binder with a suitable thermal expansion coefficient can not only regulate the TCR to a certain extent, but also play a transition role, so that the conductive functional phase is better connected to the ceramic substrate, solving the problem of thermal expansion mismatch between the resistor body and the ceramic substrate.
[0041] The present invention also provides a method for preparing the lead-free glass powder for the low-resistance ruthenium-based resistor paste described in the above technical solution, comprising the following steps:
[0042] Silicon dioxide, calcium oxide, aluminum oxide, boron oxide, magnesium oxide, sodium oxide, potassium oxide and additives are mixed according to mass percentage, and first ball milling, first drying and first crushing are performed in sequence to obtain a mixed powder;
[0043] The mixed powder is melted and then quenched to obtain glass slag;
[0044] After the glass slag is crushed, a second ball milling, a second drying and a second crushing are sequentially performed to obtain the lead-free glass powder for the low-resistance ruthenium-based resistor paste.
[0045] The invention mixes silicon dioxide, calcium oxide, aluminum oxide, boron oxide, magnesium oxide, sodium oxide, potassium oxide and additives according to mass percentage, and sequentially performs first ball milling, first drying and first crushing to obtain mixed powder.
[0046] As an implementation mode, the medium used for the first ball mill is anhydrous ethanol; the rotation speed of the first ball mill is 250-350 r / min, and in a specific embodiment, it is 300 r / min; the time of the first ball mill is 90-150 min, and in a specific embodiment, it is 120 min.
[0047] As an embodiment, after the first ball milling, the method further comprises: filtering the product after the first ball milling; the filtration is suction filtration.
[0048] As an implementation manner, the temperature of the first drying is 60-80° C., and in a specific embodiment, it is 80° C.; the time of the first drying is 20-30 minutes, and in a specific embodiment, it is 30 minutes.
[0049] As an embodiment, the first pulverization is grinding and dispersing.
[0050] After obtaining the mixed powder, the present invention melts the mixed powder and then quenches it to obtain glass slag.
[0051] As an implementation mode, the smelting is as follows: first heating to 900-1000°C, then heating to 1300-1500°C for heat preservation, and in a specific embodiment, first heating to 1000°C, then heating to 1500°C for heat preservation; the heat preservation time is 2-3h, and in a specific embodiment, it is 2h.
[0052] As an implementation manner, the heating rate of the first heating is 8-10°C / min, and in a specific embodiment, it is 10°C / min; the heating rate of the second heating is 5-7°C / min, and in a specific embodiment, it is 5°C / min.
[0053] In the first heating stage of the present invention, the oxide powders have not yet begun to melt, and a higher heating rate can be set if the equipment allows. In the second heating stage, the oxides begin to melt and react with each other. At this time, the heating is slowed down to allow the components to contact and react with each other. If the temperature is raised too quickly, the low-melting-point oxides will melt while the high-melting-point oxides will not melt, resulting in uneven composition. Slow heating can allow the first-melted oxides to fully wet the surrounding unmelted oxides, dissolve each other, and make the composition more uniform.
[0054] As an embodiment, the quenching is performed using deionized water.
[0055] After obtaining the glass slag, the present invention crushes the glass slag, and then performs a second ball milling, a second drying and a second crushing in sequence to obtain the lead-free glass powder for the low-resistance ruthenium-based resistor paste.
[0056] As an implementation mode, the medium used for the second ball mill is alcohol; the rotation speed of the second ball mill is 250-350r / min, and in a specific embodiment, it is 300r / min; the time of the second ball mill is 22-26h, and in a specific embodiment, it is 24h.
[0057] As an embodiment, after the second ball milling, the method further comprises: filtering the product after the second ball milling; the filtration is suction filtration.
[0058] As an embodiment, the temperature of the second drying is 60-80° C., and in a specific embodiment, it is 80° C.; the time of the second drying is 20-30 minutes, and in a specific embodiment, it is 30 minutes.
[0059] As an embodiment, the second pulverization is grinding and dispersing.
[0060] The present invention also provides the use of the lead-free glass powder for low-resistance ruthenium resistor paste described in the above technical solution or the lead-free glass powder for low-resistance ruthenium resistor paste prepared by the preparation method described in the above technical solution in the preparation of low-resistance ruthenium resistor paste.
[0061] The present invention also provides a low-resistance ruthenium resistor paste, comprising a conductive functional phase, a glass bonding phase and an organic carrier;
[0062] The glass bonding phase is the lead-free glass powder for low-resistance ruthenium-based resistor paste described in the above technical solution or the lead-free glass powder for low-resistance ruthenium-based resistor paste prepared by the preparation method described in the above technical solution.
[0063] As an implementation mode, the mass ratio of the conductive functional phase, the glass bonding phase and the organic carrier is 60-70:10-15:15-20, and in a specific embodiment, it is 70:12:18.
[0064] As an embodiment, the composition of the conductive functional phase includes: silver, palladium, bismuth ruthenate and manganese dioxide; the mass ratio of the total mass of the silver and palladium to the mass ratio of bismuth ruthenate and manganese dioxide is 65-75:20-30:5-10, and in a specific embodiment it is 70:25:5; the mass ratio of silver and palladium is 1:1.
[0065] As an embodiment, the particle size of the bismuth ruthenate is <60nm, and in a specific embodiment, it is ≤50nm; the particle sizes of the silver and palladium are independently <3μm, and in a specific embodiment, it is ≤2μm.
[0066] As an embodiment, the preparation method of the conductive functional phase includes the following steps: mixing silver, palladium, bismuth ruthenate and manganese dioxide according to mass percentage, ball milling, solid-liquid separation, drying and crushing the obtained solid to obtain the conductive functional phase.
[0067] As an implementation mode, the ball mill uses anhydrous ethanol as the medium; the rotation speed of the ball mill is 300r / min; the ball milling time is 120min; the solid-liquid separation is suction filtration; the drying temperature is 80°C and the time is 30min; and the crushing is grinding and dispersion.
[0068] As an implementation mode, the organic carrier comprises: an organic solvent, a thickener and an organic additive; the mass ratio of the organic solvent, the thickener and the organic additive is 70-85:6-10:1-5, and in a specific embodiment is 85:10:5.
[0069] As an embodiment, the organic solvent includes pineol and / or butyl carbitol acetate, and in a specific embodiment, it is pineol and butyl carbitol acetate; the mass ratio of pineol and butyl carbitol acetate is 60:25; the thickener is ethyl cellulose; the organic additive is soy lecithin and / or oleic acid, and in a specific embodiment, it is soy lecithin.
[0070] As an embodiment, the method for preparing the organic carrier comprises the following steps: adding a thickener to an organic solvent, heating and stirring until the thickener is completely dissolved, adding an organic additive, continuing heating and stirring, and cooling to obtain an organic carrier.
[0071] As an embodiment, the heating temperature of the heating and stirring is 75-80°C, and in the specific embodiment it is 75°C; the stirring rate of the heating and stirring is 50-80r / min, and in the specific embodiment it is 50r / min; the time for continuing heating and stirring is 20-30min, and in the specific embodiment it is 30min.
[0072] As an embodiment, the method for preparing the low-resistance ruthenium resistor slurry comprises the following steps: mixing a conductive functional phase and a glass bonding phase, and sequentially ball milling, drying and crushing to obtain a mixed powder;
[0073] The mixed powder and the organic carrier are mixed and dispersed to obtain a low-resistance ruthenium-based resistor slurry.
[0074] As an implementation mode, the medium used for the ball milling is alcohol; the rotation speed of the ball milling is 250-350 r / min, and in a specific embodiment, it is 300 r / min; the time of the ball milling is 2-3 h, and in a specific embodiment, it is 2 h.
[0075] As an embodiment, after the ball milling, the method further comprises: filtering the ball milled product; the filtration is suction filtration.
[0076] As an implementation manner, the drying temperature is 60-80° C., and in a specific embodiment, it is 80° C.; the drying time is 20-30 minutes, and in a specific embodiment, it is 30 minutes.
[0077] As an embodiment, the pulverization is grinding and dispersing.
[0078] As an embodiment, the dispersion is: premixing first, then grinding to a fineness of less than 5 μm; the premixing is carried out under stirring; the stirring rate is 1500 r / min; the premixing is carried out with a planetary mixer, and the grinding is carried out with a three-roll mill.
[0079] The present invention reduces the thermal expansion coefficient of the glass binder by changing the glass binder components, effectively reduces the TCR, solves the problems of large resistance temperature coefficient of ordinary low-resistance resistors and poor matching between the resistor body and the ceramic substrate, and can be applied to high-precision low-resistance resistor products.
[0080] The technical solutions of the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention, but they should not be construed as limiting the protection scope of the present invention.
[0081] Example 1
[0082] Preparation of a conductive functional phase: weighing raw materials of 35% silver, 35% palladium, 25% bismuth ruthenate, and 5% manganese dioxide according to mass percentage, putting them into an agate ball mill, using anhydrous ethanol as a medium, ball milling and mixing for 120 minutes at 300r / min in a ball mill, filtering, drying at 80°C for 30 minutes, grinding and dispersing, and obtaining a conductive functional phase, wherein the particle size of bismuth ruthenate is <60nm, and the particle sizes of silver and palladium are <3μm;
[0083] Preparation of glass bonding phase: weigh the raw materials by mass percentage, silicon dioxide 55%, calcium oxide 27%, aluminum oxide 10%, boron trioxide 4.4%, magnesium oxide 2%, sodium oxide 1.2%, potassium oxide 0.4% and barium oxide 2% of the total mass of the above substances, use anhydrous ethanol as the medium, ball mill at 300r / min for 120min, filter, dry the obtained solid at 80℃ for 30min, grind and disperse, and place the obtained mixed powder in a muffle furnace for smelting. The melting curve is as shown in the figure. Figure 1 , after heating to 1000°C at 10°C / min, heating to 1500°C at 5°C / min and keeping the temperature for 2h, the obtained mixture is quenched with water to obtain glass slag, the glass slag is crushed and ball milled with alcohol as the medium, the ball milling speed is 300r / min, the ball milling time is 24h, and then filtered, dried at 80°C for 30min, and ground and dispersed to obtain lead-free glass powder with a particle size of <5μm, i.e., glass bonding phase;
[0084] Preparation of an organic carrier: weigh raw materials according to mass percentage, 5% soybean lecithin, 10% ethyl cellulose, 60% pineneol, and 25% butyl carbitol acetate, first stir and heat pineneol and butyl carbitol acetate to 75° C. in a beaker at a speed of 50 r / min, add ethyl cellulose and continue stirring until completely dissolved, then add soybean lecithin, keep warm and stir for 30 minutes to obtain an organic carrier;
[0085] Preparation of slurry: weigh the raw materials according to the mass percentage, 70% of the conductive functional phase, 12% of the glass bonding phase, and 18% of the organic carrier, put the conductive functional phase and the glass bonding phase into an agate ball mill, use anhydrous ethanol as the medium, use a ball mill at 300r / min to mix for 120min, then filter, dry at 80°C for 30min, and grind and disperse to obtain a mixed powder with good dispersion. Then pre-mix the mixed powder with the organic carrier in a planetary mixer at 1500r / min, and then use a three-roll mill to fully grind to a fineness of <5μm to obtain a low-resistance ruthenium resistor slurry.
[0086] Example 2
[0087] Preparation of a conductive functional phase: weighing raw materials of 35% silver, 35% palladium, 25% bismuth ruthenate, and 5% manganese dioxide according to mass percentage, putting them into an agate ball mill, using anhydrous ethanol as a medium, ball milling and mixing for 120 minutes at 300r / min in a ball mill, filtering, drying at 80°C for 30 minutes, grinding and dispersing, and obtaining a conductive functional phase, wherein the particle size of bismuth ruthenate is <60nm, and the particle sizes of silver and palladium are <3μm;
[0088] Preparation of glass bonding phase: weigh the raw materials according to mass percentage, silicon dioxide 55%, calcium oxide 27%, aluminum oxide 10%, boron trioxide 4.4%, magnesium oxide 2%, sodium oxide 1.2%, potassium oxide 0.4% and barium oxide 4% of the total mass of the above substances, use anhydrous ethanol as the medium, ball mill at 300r / min for 120min, filter, dry the obtained solid at 80℃ for 30min, grind and disperse, and place the obtained mixed powder in a muffle furnace for smelting. The melting curve is as shown in the figure. Figure 1 , after heating to 1000°C at 10°C / min, heating to 1500°C at 5°C / min and keeping the temperature for 2h, the obtained mixture is quenched with water to obtain glass slag, the glass slag is crushed and ball milled with alcohol as the medium, the ball milling speed is 300r / min, the ball milling time is 24h, and then filtered, dried at 80°C for 30min, and ground and dispersed to obtain lead-free glass powder with a particle size of <5μm, i.e., glass bonding phase;
[0089] Preparation of an organic carrier: weigh the raw materials according to mass percentage, 5% soybean lecithin, 10% ethyl cellulose, 60% pineol, and 25% butyl carbitol acetate, first heat pineol and butyl carbitol acetate to 75°C in a beaker with stirring at a speed of 50 r / min, then add ethyl cellulose and continue stirring until completely dissolved, then add soybean lecithin, keep warm and stir for 30 minutes to obtain an organic carrier.
[0090] Preparation of slurry: weigh the raw materials according to the mass percentage, 70% of the conductive functional phase, 12% of the glass bonding phase, and 18% of the organic carrier, put the conductive functional phase and the glass bonding phase into an agate ball mill, use anhydrous ethanol as the medium, use a ball mill at 300r / min to mix for 120min, then filter, dry at 80°C for 30min, and grind and disperse to obtain a mixed powder with good dispersion. Then pre-mix the mixed powder with the organic carrier in a planetary mixer at 1500r / min, and then use a three-roll mill to fully grind to a fineness of <5μm to obtain a low-resistance ruthenium resistor slurry.
[0091] Example 3
[0092] Preparation of a conductive functional phase: weighing raw materials of 35% silver, 35% palladium, 25% bismuth ruthenate, and 5% manganese dioxide according to mass percentage, putting them into an agate ball mill, using anhydrous ethanol as a medium, ball milling and mixing for 120 minutes at 300r / min in a ball mill, filtering, drying at 80°C for 30 minutes, grinding and dispersing, and obtaining a conductive functional phase, wherein the particle size of bismuth ruthenate is <60nm, and the particle sizes of silver and palladium are <3μm;
[0093] Preparation of glass bonding phase: weigh the raw materials according to mass percentage, silicon dioxide 55%, calcium oxide 27%, aluminum oxide 10%, boron trioxide 4.4%, magnesium oxide 2%, sodium oxide 1.2%, potassium oxide 0.4% and barium oxide 6% of the total mass of the above substances, use anhydrous ethanol as the medium, ball mill at 300r / min for 120min, filter, dry the obtained solid at 80℃ for 30min, grind and disperse, and place the obtained mixed powder in a muffle furnace for smelting. The melting curve is as shown in the figure. Figure 1 , after heating to 1000°C at 10°C / min, heating to 1500°C at 5°C / min and keeping the temperature for 2h, the obtained mixture is quenched with water to obtain glass slag, the glass slag is crushed and ball milled with alcohol as the medium, the ball milling speed is 300r / min, the ball milling time is 24h, and then filtered, dried at 80°C for 30min, and ground and dispersed to obtain lead-free glass powder with a particle size of <5μm, i.e., glass bonding phase;
[0094] Preparation of an organic carrier: weigh raw materials according to mass percentage, 5% soybean lecithin, 10% ethyl cellulose, 60% pineneol, and 25% butyl carbitol acetate, first stir and heat pineneol and butyl carbitol acetate to 75° C. in a beaker at a speed of 50 r / min, add ethyl cellulose and continue stirring until completely dissolved, then add soybean lecithin, keep warm and stir for 30 minutes to obtain an organic carrier;
[0095] Preparation of slurry: weigh the raw materials according to the mass percentage, 70% of the conductive functional phase, 12% of the glass bonding phase, and 18% of the organic carrier, put the conductive functional phase and the glass bonding phase into an agate ball mill, use anhydrous ethanol as the medium, use a ball mill at 300r / min to mix for 120min, then filter, dry at 80°C for 30min, and grind and disperse to obtain a mixed powder with good dispersion. Then pre-mix the mixed powder with the organic carrier in a planetary mixer at 1500r / min, and then use a three-roll mill to fully grind to a fineness of <5μm to obtain a low-resistance ruthenium resistor slurry.
[0096] Example 4
[0097] Preparation of a conductive functional phase: weighing raw materials of 35% silver, 35% palladium, 25% bismuth ruthenate, and 5% manganese dioxide according to mass percentage, putting them into an agate ball mill, using anhydrous ethanol as a medium, ball milling and mixing for 120 minutes at 300r / min in a ball mill, filtering, drying at 80°C for 30 minutes, grinding and dispersing, and obtaining a conductive functional phase, wherein the particle size of bismuth ruthenate is <60nm, and the particle sizes of silver and palladium are <3μm;
[0098] Preparation of glass bonding phase: weigh the raw materials according to mass percentage, silicon dioxide 55%, calcium oxide 27%, aluminum oxide 10%, boron trioxide 4.4%, magnesium oxide 2%, sodium oxide 1.2%, potassium oxide 0.4% and zinc oxide 2% of the total mass of the above substances, use anhydrous ethanol as the medium, ball mill at 300r / min for 120min, filter, dry the obtained solid at 80℃ for 30min, grind and disperse, and place the obtained mixed powder in a muffle furnace for smelting. The melting curve is as shown in the figure. Figure 1 , after heating to 1000°C at 10°C / min, heating to 1500°C at 5°C / min and keeping the temperature for 2h, the obtained mixture is quenched with water to obtain glass slag, the glass slag is crushed and ball milled with alcohol as the medium, the ball milling speed is 300r / min, the ball milling time is 24h, and then filtered, dried at 80°C for 30min, and ground and dispersed to obtain lead-free glass powder with a particle size of <5μm, i.e., glass bonding phase;
[0099] Preparation of an organic carrier: weigh raw materials according to mass percentage, 5% soybean lecithin, 10% ethyl cellulose, 60% pineneol, and 25% butyl carbitol acetate, first stir and heat pineneol and butyl carbitol acetate to 75° C. in a beaker at a speed of 50 r / min, add ethyl cellulose and continue stirring until completely dissolved, then add soybean lecithin, keep warm and stir for 30 minutes to obtain an organic carrier;
[0100] Preparation of slurry: weigh the raw materials according to the mass percentage, 70% of the conductive functional phase, 12% of the glass bonding phase, and 18% of the organic carrier, put the conductive functional phase and the glass bonding phase into an agate ball mill, use anhydrous ethanol as the medium, use a ball mill at 300r / min to mix for 120min, then filter, dry at 80°C for 30min, and grind and disperse to obtain a mixed powder with good dispersion. Then pre-mix the mixed powder with the organic carrier in a planetary mixer at 1500r / min, and then use a three-roll mill to fully grind to a fineness of <5μm to obtain a low-resistance ruthenium resistor slurry.
[0101] Example 5
[0102] Preparation of a conductive functional phase: weighing raw materials of 35% silver, 35% palladium, 25% bismuth ruthenate, and 5% manganese dioxide according to mass percentage, putting them into an agate ball mill, using anhydrous ethanol as a medium, ball milling and mixing for 120 minutes at 300r / min in a ball mill, filtering, drying at 80°C for 30 minutes, grinding and dispersing, and obtaining a conductive functional phase, wherein the particle size of bismuth ruthenate is <60nm, and the particle sizes of silver and palladium are <3μm;
[0103] Preparation of glass bonding phase: weigh the raw materials according to mass percentage, silicon dioxide 55%, calcium oxide 27%, aluminum oxide 10%, boron trioxide 4.4%, magnesium oxide 2%, sodium oxide 1.2%, potassium oxide 0.4% and zinc oxide 4% of the total mass of the above substances, use anhydrous ethanol as the medium, ball mill at 300r / min for 120min, filter, dry the obtained solid at 80℃ for 30min, grind and disperse, and place the obtained mixed powder in a muffle furnace for smelting. The melting curve is as shown in the figure. Figure 1 , after heating to 1000°C at 10°C / min, heating to 1500°C at 5°C / min and keeping the temperature for 2h, the obtained mixture is quenched with water to obtain glass slag, the glass slag is crushed and ball milled with alcohol as the medium, the ball milling speed is 300r / min, the ball milling time is 24h, and then filtered, dried at 80°C for 30min, and ground and dispersed to obtain lead-free glass powder with a particle size of <5μm, i.e., glass bonding phase;
[0104] Preparation of an organic carrier: weigh raw materials according to mass percentage, 5% soybean lecithin, 10% ethyl cellulose, 60% pineneol, and 25% butyl carbitol acetate, first stir and heat pineneol and butyl carbitol acetate to 75° C. in a beaker at a speed of 50 r / min, add ethyl cellulose and continue stirring until completely dissolved, then add soybean lecithin, keep warm and stir for 30 minutes to obtain an organic carrier;
[0105] Preparation of slurry: weigh the raw materials according to the mass percentage, 70% of the conductive functional phase, 12% of the glass bonding phase, and 18% of the organic carrier, put the conductive functional phase and the glass bonding phase into an agate ball mill, use anhydrous ethanol as the medium, use a ball mill at 300r / min to mix for 120min, then filter, dry at 80°C for 30min, and grind and disperse to obtain a mixed powder with good dispersion. Then pre-mix the mixed powder with the organic carrier in a planetary mixer at 1500r / min, and then use a three-roll mill to fully grind to a fineness of <5μm to obtain a low-resistance ruthenium resistor slurry.
[0106] Example 6
[0107] Preparation of a conductive functional phase: weighing raw materials according to mass percentage of silver 35%, palladium 35%, bismuth ruthenate 25%, and manganese dioxide 5%, putting them into an agate ball mill, using anhydrous ethanol as a medium, ball milling and mixing for 120 minutes at 300r / min in a ball mill, filtering, drying at 80°C for 30 minutes, grinding and dispersing, to obtain a conductive functional phase, wherein the particle size of bismuth ruthenate is <60nm, and the particle sizes of silver and palladium are <3μm;
[0108] Preparation of glass bonding phase: weigh the raw materials according to mass percentage, silicon dioxide 55%, calcium oxide 27%, aluminum oxide 10%, boron trioxide 4.4%, magnesium oxide 2%, sodium oxide 1.2%, potassium oxide 0.4% and zinc oxide 6% of the total mass of the above substances, use anhydrous ethanol as the medium, ball mill at 300r / min for 120min, filter, dry the obtained solid at 80℃ for 30min, grind and disperse, and place the obtained mixed powder in a muffle furnace for smelting. The melting curve is as shown in the figure. Figure 1 , after heating to 1000°C at 10°C / min, heating to 1500°C at 5°C / min and keeping the temperature for 2h, the obtained mixture is quenched with water to obtain glass slag, the glass slag is crushed and ball milled with alcohol as the medium, the ball milling speed is 300r / min, the ball milling time is 24h, and then filtered, dried at 80°C for 30min, and ground and dispersed to obtain lead-free glass powder with a particle size of <5μm, i.e., glass bonding phase;
[0109] Preparation of an organic carrier: weigh raw materials according to mass percentage, 5% soybean lecithin, 10% ethyl cellulose, 60% pineneol, and 25% butyl carbitol acetate, first stir and heat pineneol and butyl carbitol acetate to 75° C. in a beaker at a speed of 50 r / min, add ethyl cellulose and continue stirring until completely dissolved, then add soybean lecithin, keep warm and stir for 30 minutes to obtain an organic carrier;
[0110] Preparation of slurry: weigh the raw materials according to the mass percentage, 70% of the conductive functional phase, 12% of the glass bonding phase, and 18% of the organic carrier, put the conductive functional phase and the glass bonding phase into an agate ball mill, use anhydrous ethanol as the medium, use a ball mill at 300r / min to mix for 120min, then filter, dry at 80°C for 30min, and grind and disperse to obtain a mixed powder with good dispersion. Then pre-mix the mixed powder with the organic carrier in a planetary mixer at 1500r / min, and then use a three-roll mill to fully grind to a fineness of <5μm to obtain a low-resistance ruthenium resistor slurry.
[0111] Comparative Example 1
[0112] Preparation of a conductive functional phase: weighing raw materials of 35% silver, 35% palladium, 25% bismuth ruthenate, and 5% manganese dioxide according to mass percentage, putting them into an agate ball mill, using anhydrous ethanol as a medium, ball milling and mixing for 120 minutes at 300r / min in a ball mill, filtering, drying at 80°C for 30 minutes, grinding and dispersing, and obtaining a conductive functional phase, wherein the particle size of bismuth ruthenate is <60nm, and the particle sizes of silver and palladium are <3μm;
[0113] Preparation of glass bonding phase: weigh the raw materials by mass percentage, silicon dioxide 55%, calcium oxide 27%, aluminum oxide 10%, boron trioxide 4.4%, magnesium oxide 2%, sodium oxide 1.2%, potassium oxide 0.4%, use anhydrous ethanol as the medium, ball mill at 300r / min for 120min, filter, dry the obtained solid at 80℃ for 30min, grind and disperse, and place the obtained mixed powder in a muffle furnace for smelting. The melting curve is as shown in the figure. Figure 1 , after heating to 1000°C at 10°C / min, heating to 1500°C at 5°C / min and keeping the temperature for 2h, the obtained mixture is quenched with water to obtain glass slag, the glass slag is crushed and ball milled with alcohol as the medium, the ball milling speed is 300r / min, the ball milling time is 24h, and then filtered, dried at 80°C for 30min, and ground and dispersed to obtain a glass bonding phase with a particle size of <5μm;
[0114] Preparation of an organic carrier: weigh raw materials according to mass percentage, 5% soybean lecithin, 10% ethyl cellulose, 60% pineneol, and 25% butyl carbitol acetate, first stir and heat pineneol and butyl carbitol acetate to 75° C. in a beaker at a speed of 50 r / min, add ethyl cellulose and continue stirring until completely dissolved, then add soybean lecithin, keep warm and stir for 30 minutes to obtain an organic carrier;
[0115] Preparation of slurry: weigh the raw materials according to the mass percentage, 70% of the conductive functional phase, 12% of the glass bonding phase, and 18% of the organic carrier, put the conductive functional phase and the glass bonding phase into an agate ball mill, use anhydrous ethanol as the medium, use a ball mill at 300r / min to mix for 120min, filter, dry at 80°C for 30min, grind and disperse to obtain a mixed powder with good dispersion, and then pre-mix the mixed powder with the organic carrier in a planetary mixer at 1500r / min, and then use a three-roll mill to fully grind to a fineness of <5μm to obtain a resistor slurry.
[0116] Comparative Example 2
[0117] Preparation of a conductive functional phase: weighing raw materials of 35% silver, 35% palladium, 25% bismuth ruthenate, and 5% manganese dioxide according to mass percentage, putting them into an agate ball mill, using anhydrous ethanol as a medium, ball milling and mixing for 120 minutes at 300r / min in a ball mill, filtering, drying at 80°C for 30 minutes, grinding and dispersing, and obtaining a conductive functional phase, wherein the particle size of bismuth ruthenate is <60nm, and the particle sizes of silver and palladium are <3μm;
[0118] Preparation of glass bonding phase: weigh the raw materials according to mass percentage, lead oxide 60%, silicon dioxide 30%, aluminum oxide 5%, boron oxide 5%, use anhydrous ethanol as the medium, ball mill at 300r / min for 120min, filter, dry the obtained solid at 80℃ for 30min, grind and disperse, and place the obtained mixed powder in a muffle furnace for smelting. The melting curve is as follows: Figure 1 , after heating to 1000°C at 10°C / min, heating to 1500°C at 5°C / min and keeping the temperature for 2h, the obtained mixture is quenched with water to obtain glass slag, the glass slag is crushed and ball milled with alcohol as the medium, the ball milling speed is 300r / min, the ball milling time is 24h, and then filtered, dried at 80°C for 30min, and ground and dispersed to obtain a glass bonding phase with a particle size of <5μm;
[0119] Preparation of an organic carrier: weigh raw materials according to mass percentage, 5% soybean lecithin, 10% ethyl cellulose, 60% pineneol, and 25% butyl carbitol acetate, first stir and heat pineneol and butyl carbitol acetate to 75° C. in a beaker at a speed of 50 r / min, add ethyl cellulose and continue stirring until completely dissolved, then add soybean lecithin, keep warm and stir for 30 minutes to obtain an organic carrier;
[0120] Preparation of slurry: weigh the raw materials according to the mass percentage, 70% of the conductive functional phase, 12% of the glass bonding phase, and 18% of the organic carrier, put the conductive functional phase and the glass bonding phase into an agate ball mill, use anhydrous ethanol as the medium, use a ball mill at 300r / min to mix for 120min, filter, dry at 80°C for 30min, grind and disperse to obtain a mixed powder with good dispersion, and then pre-mix the mixed powder with the organic carrier in a planetary mixer at 1500r / min, and then use a three-roll mill to fully grind to a fineness of <5μm to obtain a resistor slurry.
[0121] Performance Testing
[0122] The resistor pastes of the above-mentioned Examples 1 to 6 and Comparative Examples 1 to 2 were respectively printed on an alumina ceramic substrate by screen printing, dried at 180°C for 30 minutes, sintered in a belt tunnel sintering furnace at 850±10°C, with a sintering cycle of 30 minutes and a peak holding time of 5 minutes to prepare test samples, and the following performance tests were performed:
[0123] Square resistance: square resistance test is carried out according to method 105 electronic paste square resistance test method in SJ / T11512-2015 performance test method of electronic paste for integrated circuits.
[0124] TCR: According to SJ / T11512-2015 Performance Test Methods for Electronic Pastes for Integrated Circuits, Method 301 Electronic Paste Temperature Coefficient Test Method, the square resistance of the resistor at 25°C and 125°C is tested respectively, and the TCR is calculated.
[0125] The test results of the above embodiments and comparative examples are shown in Table 1.
[0126] Table 1 Comparison of resistor paste performance
[0127] Resistor Paste Square resistance (Ω / □) TCR(ppm / ℃) Thermal expansion coefficient α(ppm / ℃) Example 1 6.76 473 5.8 Example 2 5.69 496 5.9 Example 3 6.47 408 5.2 Example 4 5.49 427 4.8 Example 5 6.82 300 4.1 Example 6 5.96 317 4.3 Comparative Example 1 5.08 531 6.6 Comparative Example 2 3.45 625 7.2
[0128] It can be seen from Table 1 that the thermal expansion coefficient of the glass adhesive used in Examples 1 to 6 increases with the increase of the additive content, and an excellent low-resistance ruthenium resistor paste with a square resistance value of 1 to 10Ω / □ and high stability can be obtained.
[0129] Comparison of Examples 1 to 6 with Comparative Example 1 shows that reducing the thermal expansion coefficient of the glass binder can effectively reduce the TCR value of the resistor paste and has an impact on the conductive mechanism of the resistor paste (such as Figure 2 ) analysis shows that the smaller the thermal expansion coefficient of the glass binder is than that of the conductive particles, the closer the conductive particles tend to be to each other when the temperature rises, which to a certain extent offsets the potential barrier between the conductive particles caused by the increase in temperature, reduces the contact resistance, and thus achieves the regulation of TCR.
[0130] Comparing Examples 1 to 6 with Comparative Example 2, the TCR value of lead-containing glass is slightly higher than that of lead-free glass, and the square resistance values are both between 1 and 10Ω / □.
[0131] It can be seen from the above experimental results that the lead-free glass powder for the low-resistance ruthenium-based resistor paste of the present invention reduces the thermal expansion coefficient of glass by changing the type and ratio of additives, thereby reducing the potential barrier between the conductive particles after the temperature rises, and then reducing the contact resistance between the conductive particles, effectively achieving a reduction in TCR, and to a certain extent can replace lead-containing glass powder, meeting the performance and environmental friendliness requirements of high-precision low-resistance resistor products.
[0132] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A lead-free glass powder for low-resistance ruthenium-based resistor paste, characterized in that: Preparation of raw materials including basic ingredients and additives; The basic components include, based on 100% by mass, 50-65% silicon dioxide, 20-30% calcium oxide, 8-12% aluminum oxide, 4-6% boron trioxide, 1-3% magnesium oxide, 1-2% sodium oxide and 0.2-0.5% potassium oxide; The mass of the additive is 2-6% of the mass of the basic component; The additives include barium oxide and / or zinc oxide; The softening temperature of the lead-free glass powder for the low-resistance ruthenium resistor paste is 550-730° C., and the particle size is ≤5 μm.
2. The method for preparing the lead-free glass powder for low-resistance ruthenium-based resistor paste according to claim 1, characterized in that: The following steps are involved: Silicon dioxide, calcium oxide, aluminum oxide, boron oxide, magnesium oxide, sodium oxide, potassium oxide and additives are mixed according to mass percentage, and first ball milling, first drying and first crushing are performed in sequence to obtain a mixed powder; The mixed powder is melted and then quenched to obtain glass slag; After the glass slag is crushed, a second ball milling, a second drying and a second crushing are sequentially performed to obtain the lead-free glass powder for the low-resistance ruthenium-based resistor paste.
3. The preparation method according to claim 2, characterized in that: The smelting is as follows: first heating the temperature to 900-1000° C., then heating the temperature to 1300-1500° C. and keeping the temperature; the keeping temperature time is 2 hours.
4. The preparation method according to claim 3, characterized in that: The heating rate of the first heating is 8-10°C / min; the heating rate of the second heating is 5-7°C / min.
5. Use of the lead-free glass powder for low-resistance ruthenium resistor paste according to claim 1 or the lead-free glass powder for low-resistance ruthenium resistor paste prepared by the preparation method according to any one of claims 2 to 4 in the preparation of low-resistance ruthenium resistor paste.
6. A low-resistance ruthenium resistor slurry, characterized in that: It includes a conductive functional phase, a glass bonding phase and an organic carrier; The glass bonding phase is the lead-free glass powder for low-resistance ruthenium resistor paste according to claim 1 or the lead-free glass powder for low-resistance ruthenium resistor paste prepared by the preparation method according to any one of claims 2 to 4.
7. The low-resistance ruthenium resistor paste according to claim 6, characterized in that: The mass ratio of the conductive functional phase, the glass bonding phase and the organic carrier is 60-70:10-15:15-20.
8. The low-resistance ruthenium resistor paste according to claim 6, characterized in that: The conductive functional phase comprises silver, palladium, bismuth ruthenate and manganese dioxide.
9. The low-resistance ruthenium resistor paste according to claim 6, characterized in that: The organic carrier comprises: an organic solvent, a thickener and an organic additive.
10. The low-resistance ruthenium resistor paste according to claim 9, characterized in that: The organic solvent includes terpineol and / or butyl carbitol acetate; the thickener is ethyl cellulose; and the organic additive is soybean lecithin and / or oleic acid.